2019
DOI: 10.1002/jssc.201801177
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4/reduced graphene oxide-carbon nanotubes composite for the magnetic solid-phase extraction and HPLC determination of sulfonamides in milk

Abstract: A novel magnetic adsorbent Fe3O4/reduced graphene oxide‐carbon nanotubes, was prepared by one‐pot solvothermal synthesis method. It was characterized by scanning electron microscopy, X‐ray powder diffraction and vibrating sample magnetometry. The diameter of Fe3O4 microparticles was about 350 nm, which were covered by carbon nanotubes and reduced graphene oxide sheets, while carbon nanotubes inserted between the reduced graphene oxide sheets effectively prevented their aggregation. The composite had large surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…For this purpose, iron (III) chloride hexahydrate, sodium acetate, GO and CNTs were added in a Teflon-liner and the suspension was heated at 200 • C for 10 h. It was found that the Fe 3 O 4 nanoparticles were covered with RGO and CNTs, while CNTs were inserted between the RGO sheets in order to prevent the aggregation of the RGO sheets. The novel sorbent was used for the MSPE of sulfonamides from milk prior to their determination with HPLC-UV [73]. Pinsrithong and Bunkoed prepared a hierarchical porous polypyrrole-coated nanostructured composite of RGO and Fe 3 O 4 nanoparticles.…”
Section: Nanocomposites Of Reduced Go With Fe 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…For this purpose, iron (III) chloride hexahydrate, sodium acetate, GO and CNTs were added in a Teflon-liner and the suspension was heated at 200 • C for 10 h. It was found that the Fe 3 O 4 nanoparticles were covered with RGO and CNTs, while CNTs were inserted between the RGO sheets in order to prevent the aggregation of the RGO sheets. The novel sorbent was used for the MSPE of sulfonamides from milk prior to their determination with HPLC-UV [73]. Pinsrithong and Bunkoed prepared a hierarchical porous polypyrrole-coated nanostructured composite of RGO and Fe 3 O 4 nanoparticles.…”
Section: Nanocomposites Of Reduced Go With Fe 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…The term molecularly imprinted polymer was further searched in the results of polymer. As shown, carbon [28,30,40,41,46,[107][108][109][110][111][112][113][114] materials are the most widely used adsorbents for enrichments of sulfonamides. Because the key for efficient enrichments of sulfonamides is to improve the adsorption capacity of the adsorbent, investigations of the adsorption properties and mechanisms are necessary.…”
Section: Adsorbentmentioning
confidence: 99%
“…Carbon materials used for sulfonamide enrichment include GO [40,[107][108][109][110][111][112][113][114][115][116][117][118][119], CNTs [30,33,46,110,111], graphene [112][113][114], and other carbon materials. These all possess the merits of good electrical, mechanical, physical, and chemical properties, and a very high surface to volume ratio [115].…”
Section: Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene is a two‐dimensional honeycomb lattice material composed of carbon atoms . Due to the large specific area, good thermal and chemical stability, and π‐π electrostatic stacking properties graphene‐based materials have a variety of applications in modern sample preparation techniques , and graphene‐based sorbents have been used for extraction of polycyclic aromatic hydrocarbons , pesticide residues , mycotoxins , antibiotic drugs , nicotine , phytohormones , heavy metals , aromatic amines , and siloxanes in various samples. And recent studies have illustrated that graphene‐based materials have high adsorption capacity for TSNAs .…”
Section: Introductionmentioning
confidence: 99%